Pelvic floor muscle training in women with stress urinary incontinence causes hypertrophy of the urethral sphincters and reduces bladder neck mobility during coughing. Issue 8 (17th July 2013) - McLean, Linda; Varette, Kevin; Gentilcore‐Saulnier, Evelyne; Harvey, Marie‐Andree; Baker, Kevin; Sauerbrei, Eric
Abstract Aims The purpose of this study was to determine the effect of a 12‐week pelvic floor muscle (PFM) training program on urethral morphology and mobility in women with stress urinary incontinence (SUI). Methods Forty women with SUI were randomly assigned to one of two groups: the treatment group received 12 weekly physiotherapy sessions during which they learned how to properly contract their pelvic floor muscles (PFMs) and a home exercise program was prescribed, reviewed, and progressed; the control group received no treatment. Before and after the 12‐week study period, ultrasound imaging was used to evaluate bladder neck position and mobility during coughing and Valsalva maneuver in supine and in standing, as well as urethral morphology. Secondary outcome measures included a 3‐day bladder diary, 30‐min pad test, the Incontinence Impact Questionnaire (IIQ‐7) and the Urogenital Distress Inventory (UDI‐6). Results The women in the treatment group demonstrated reduced bladder neck mobility during coughing and increased cross‐sectional area of their urethra after as compared to before the training. These changes were not evident in the control group. No differences in the resting position of the bladder neck or in bladder neck excursion during Valsalva maneuver were noted in either group. Concomitantly the women in the treatment group demonstrated significant improvements in the 3‐day bladder diary and IIQ‐7 after the PFM training and improved significantly more than the control group. Conclusion Physiotherapist‐supervised PFM training reduces bladder neck motion during coughing, and results in hypertrophy of the urethral sphincter in women who present with SUI. Neurourol. Urodynam. 32:1096–1102, 2013. © 2013 Wiley Periodicals, Inc.